Constrained inefficiency and optimal taxation with uninsurable risks - Piero Gottardi; Atsushi Kajii; Tomoyuki Nakajima (Federal Reserve Bank of Atlanta, 2014)
When individuals' labor and capital income are subject to uninsurable idiosyncratic risks, should capital and labor be taxed, and if so, how? In a two-period general equilibrium model with production, we derive a decomposition formula of the welfare effects of these taxes into insurance and distribution effects. This method allows us to determine how the sign of the optimal taxes on capital and labor depends on the nature of the shocks, the degree of heterogeneity among consumers' income, and the way in which the tax revenue is used to provide lump sum transfers to consumers. When shocks affect primarily labor income and heterogeneity is small, the optimal tax on capital is positive. However, in other cases, a negative tax on capital improves.
Keywords: D52; H21; 330; optimal linear taxes; incomplete markets; constrained efficiency